A photocatalytic decarboxylative/defluorinative [4 + 3] annulation of o-hydroxyphenylacetic acids and trifluoromethyl alkenes: synthesis of fluorinated dihydrobenzoxepines. Issue 22 (8th October 2018) - Chen, Haoguo; He, Yuwei; Zhou, Lei
Abstract : A photocatalytic decarboxylative/defluorinative [4 + 3] annulation of o -hydroxyphenylacetic acids and trifluoromethyl alkenes was developed. The reaction led to fluorinated dihydrobenzoxepines through two consecutive C–F substitutions in a CF3 group. Abstract : A photocatalytic decarboxylative/defluorinative [4 + 3] annulation of o -hydroxyphenylacetic acids and trifluoromethyl alkenes was developed. The reaction affords fluorinated dihydrobenzoxepines via two consecutive C–F substitutions in a CF3 group.